Assessment of Financial Benefits of Selected Mezzanine Financing Instruments - Tetřevová Liběna; Svědík Jan (Vilnius Gediminas Technical University, 2016)
The paper deals with the problems of assessment of financial benefits of subordinated loans and convertible bonds. The paper authors aim to propose and verify methodology for assessment of the financial benefits of subordinated loans and convertible bonds.
Hodnocení finanční výhodnosti vybraných instrumentů mezaninového financování
Keywords: financial sources; mezzanine instruments; subordinated loans; convertible bonds; assessment of financial benefits; finanční zdroje; mezaninové instrumenty; podřízené úvěry; konvertibilní dluhopisy; hodnocení finanční výhodnosti